2005
DOI: 10.1002/smll.200500181
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a Silicon Nanowire Vertical Surround‐Gate Field‐Effect Transistor

Abstract: A generic process for fabricating vertical surround‐gate field‐effect transistors (FETs) from epitaxially grown silicon nanowires is presented. The process is demonstrated using n‐type Si nanowires grown on a p‐type substrate in ultrahigh vacuum using a Au catalyst. The process consists of various deposition and etching steps; no chemical or mechanical polishing is required. Individual as well as arrays of vertical surround‐gate FETs can be fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
258
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(260 citation statements)
references
References 19 publications
1
258
0
1
Order By: Relevance
“…Higher performance FETs could come from Silicon nanowires, which are fairly easy to grow and have properties that can be used in transistors (Schmidt et al 2006;Yoon et al 2006), and Carbon nanotubes, which are also commonly available and can make transistors (Martel et al 2001;Chen et al 2008). Assembly of these nanoscale objects into useful circuitry is a challenge.…”
Section: New Transistor Technologymentioning
confidence: 99%
“…Higher performance FETs could come from Silicon nanowires, which are fairly easy to grow and have properties that can be used in transistors (Schmidt et al 2006;Yoon et al 2006), and Carbon nanotubes, which are also commonly available and can make transistors (Martel et al 2001;Chen et al 2008). Assembly of these nanoscale objects into useful circuitry is a challenge.…”
Section: New Transistor Technologymentioning
confidence: 99%
“…Suk et al have shown transistor data for 10-nm lateral Si wires with a full wrap gate using SiO 2 as gate dielectric [3]. In the vertical geometry, many groups are currently working with epitaxially grown nanowires [4]- [7]. An important motivation here is the possibility of growing group III-V nanowires directly on Si, as well as highly lattice-mismatched semiconductor heterostructures within a wire [8]- [10].…”
mentioning
confidence: 99%
“…In principle, similar fabrication schemes can be used with other nanowire/substrate combinations. Similar strategy has been employed for the realization of a VSG-FET using Si nanowire grown epitaxially by CVD on a (111)-oriented p-type Si substrate (Schmidt et al, 2006). The surround gate allows better electrostatic gate control of the conducting channel and offers the potential to drive more current per device area than is possible in a conventional planar architecture (Wang et al, 2004).…”
Section: Patterned Growth Of Vertical Nanowiresmentioning
confidence: 99%